PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN HUSH PUPPIES DI MARKET PLACE SHOPEE TANGERANG KOTA - Rassya Saputra, Thitan; Senen (Journal of Research and Publication Innovation, 2024)
This research aims to examine the influence of service quality and brand image on customer purchasing decisions for Hush Puppies at Market Place Shopee Tangerang City. This type of research is quantitative with 96 respondents. This research uses a quantitative analysis method, namely using in-depth data analysis in the form of numbers. The sampling method used in this research is the Rao Purba sample. The population size in the research cannot be known with certainty. Data processing and analysis techniques use descriptive analysis, data instrument testing, classical assumption testing, correlation and determination testing, hypothesis testing. The results of research tests on service quality and brand image have a positive and significant effect on purchasing decision with the regression equation Y = 8.930+0.446X1+0.288X2. The correlation coefficient value is 0.609, meaning it has a strong relationship. The coefficient of determination value is 37.1% while the remaining 62.9% is influenced by other factors. Hypothesis testing obtained a value of Fcount > Ftable or (27.474 > 3.093). This H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence of service quality and brand image on purchasing decisions.